IMPROVING THE STUDENTSâ READING COMPREHENSION THROUGH NUMBERED HEADS TOGETHER TECHNIQUE - Purnomo, Suud (Journal on English as a Foreign Language (JEFL), 2012)
The method applied in this research was a classroom action research. After three cycles consisting of two meetings each were conducted, the appropriate model of NHT technique in teaching reading encompassed the following steps: (1) leading students to the topic by giving some questions and/or showing a picture(s), (2) connecting the topic with the studentsâ real experience, (3) introducing the topic and explaining the instructional objectives, (4) assigning students to predict the words used in the text, (5) informing students about the things they should do in their groups, (6) reading the text clearly, loudly, and slowly and asking some students to re-read the text, (7) clarifying the difficult words and discussing the words the students have predicted, (8) asking students to predict the content, (9) giving individual task to the students, (10) assigning students to put their heads together and discuss the answer they have done individually, (11) checking the groupsâ answers, and (12) asking students to conclude the lesson. The finding showed that NHT technique was successful in improving studentsâ reading comprehension. The improvement could be seen from the increase of studentsâ average reading scores. Besides, the finding also showed that NHT technique was effective in enhancing the studentsâ participation, especially in raising their hands competitively to answer the questions during the answer-checking session.Keywords: NHT technique, improve, reading comprehension